2013
DOI: 10.1159/000353236
|View full text |Cite
|
Sign up to set email alerts
|

Direct Fetal Intravenous Immunoglobulin Infusion as an Adjunct to Intrauterine Fetal Blood Transfusion in Rhesus-Allommunized Pregnancies: A Pilot Study

Abstract: Objectives: To study the usefulness of direct fetal intravenous immunoglobulin (IVIG) infusion along with intrauterine transfusion (IUT) in the management of severe fetal anemia in rhesus (Rh) alloimmunized pregnancies. Methods: Thirty-four consecutive Rh-isoimmunized pregnant women who required serial IUTs received either blood alone (control group, n = 16) or IVIG and blood (study group, n = 18). Pregnancies were followed up to delivery, and fetal outcome was recorded. The rate of fall of hematocrit was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Recently, a prospective case-control study in 34 women compared IUT with fetal IVIG infusion to IUT alone and described a slower hematocrit decline after IUT in the IVIG group [89]. Similar results were found before, but no impact on perinatal outcome was reported [87,88].…”
Section: Intravenous Immunoglobulins (Ivig)supporting
confidence: 55%
See 1 more Smart Citation
“…Recently, a prospective case-control study in 34 women compared IUT with fetal IVIG infusion to IUT alone and described a slower hematocrit decline after IUT in the IVIG group [89]. Similar results were found before, but no impact on perinatal outcome was reported [87,88].…”
Section: Intravenous Immunoglobulins (Ivig)supporting
confidence: 55%
“…Few fetal therapy centers administrate IVIG directly to the fetus after gaining intraperitoneal or intravascular access [87][88][89]. The increased volume given to the fetus could lead to cardiac compromise.…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
“…However, the results are not promising and the fetus still requires transfusion. Deka et al studied the effect of high dose of IVIg in iso-immunized mother as primary therapy in six patients and found it to be beneficial [31,32]. Deka et al had also studied the effect of direct fetal intravenous transfusion of immunoglobulins and reported that these fetuses required less number of transfusions and the rate of fall in fetal hemoglobin was slower in the intervention group [31,32].…”
Section: Methodsmentioning
confidence: 99%
“…Performing the IUT procedure requires a high level of skill and so reducing the number of transfusions is desirable to prevent the risk of procedure-related (PR) complications including the risk of infections transmitted via blood components. 17 , 18 PR complications include membrane rupture, preterm delivery, chorioamnionitis, and foetal and neonatal death. 8 , 19 The most serious complication during the procedure is foetal distress which can result in emergency preterm delivery or foetal death.…”
Section: Introductionmentioning
confidence: 99%